RARE-42. PRIMARY INTRACRANIAL SARCOMA WITH DICER1-MUTATION - TREATMENT RESULTS OF A NEW MOLECULAR ENTITY. (4th December 2020) - Diaz, Rosdali; Mynarek, Martin; Casavilca, Sandro; Aptomizer, Antonio Wachtel; Mora, Pamela; Koelsche, Christian; Von Deimling, Andreas; Schüller, Ulrich; Sernaque, Raymundo; Sarria, Gustavo; Negreiros, Tatiana; Ojeda, Luis; et al.
Abstract: OBJECTIVE: An unexpectedly high incidence of sarcomas of the Central Nervous System (SCNS) was recently observed in Peru. We describe clinical and biological characteristics of the disease. METHODS: Seventy pediatric patients with primary SCNS diagnosed between January 2005 and June 2018 were analyzed. DNA methylation profiling and gene panel sequencing was available from 28 and 27 tumors, respectively. RESULTS: Median age was 6 years (range 2–17.5), 66/70 patients had supratentorial tumors, 56 patients intratumoral hemorrhage at diagnosis. Three patients fulfilled clinical criteria of NF1; 35 had café-au-lait spots and/or freckling. DNA-methylation profiling classified 28/28 as "intracranial spindle cell sarcoma with rhabdomyosarcoma-like features and DICER1 mutations". DICER1 mutations were found in 26/27, TP53 mutations in 22/27, and RAS -pathway gene mutations ( NF1, KRAS, NRAS ) in 19/27 tumors, all of which were somatic (germline control available in n=19 cases). Survival was analyzed in 57 patients with non-metastatic disease who received adjuvant therapy. Two patients had metastatic disease, eleven did not receive or abandoned treatment. Two-year OS was 66.3% (95%-CI: 54–81%), 2-year PFS 51% (38–67%). PFS was highest in patients treated with postoperative ICE chemotherapy followed by radiotherapy and ICE (2y-EFS 79% [59–100%], n=18) and worse after upfront radiotherapy followed by ICE (40% [19–85%]; n=10) or VAC (50% [28–88%], n=12) and radiotherapy only (21% [6–71%], n=11; p=0.008). CONCLUSION: Primary SCNS with DICER1 mutation have an aggressive clinical course. A combination of chemotherapy and radiotherapy seems beneficial. A link to a cancer predisposition syndrome could not be established so far.